Layout Perpustakaan Sebagai Daya Tarik Perpustakaan Untuk Meningkatkan Minat Baca Pengguna Perpustakaan Fakultas Hukum Universitas Udayana - Wulandari, Ratna; Suhartika, I Putu; Ginting, Richard Togaranta (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2016)
ABSTRACT The title of this study is The Layout of Library to Improve Reading Interest of the users in the library of Faculty of Law Udayana Uviversity. This type of research is descriptive quantitative. This study aims are to determine the layout of the library of the Faculty of Law Udayana University and to determine the influence or relationship betwen layout library and reading interest. The expected benefits of this research are for educational institutions and for the library it self. This study is located in the Library of the Faculty of Law Udayana University. Students who become members of the library of the Faculty of Law, University of Udayana registered in 2016 is used as the population of this study. Samples in this study is calculated using the formula slovin, while the sample collection technique used is Probability Sampling. This study uses questionnaires as data collection techniques. The techniques of data analysis used in this study is a simple linear regression analysis while using the formula Y = a + bX . Keywords: Layout, Interests Read, Library, Research